Pengembangan Media Labirin Berbasis Loose Part untuk Perkembangan Kognitif Anak Usia 4-5 tahun - Siti Maimanah; Musayyadah; Danang Prasetyo (Universitas Islam Tribakti Lirboyo Kediri, 2022)
Learning media is only a tool for the success of the teaching and learning process, as a component of the success of the teaching and learning process, the procurement of learning media is a must that must exist. It is suggested that learning media should consist of elements that can develop the full potential of children and can be a solution to obstacles in the learning process. This study uses a research and development model from Borg and Gall, the location of this research is RA Nurul Hidayah Omben Sampang. The number of classes at RA Nurul Hidayah is quite large, namely two classes for group A and three classes for group B. This study focuses on group A1 according to the findings at the pre-study stage. Data collection techniques used are observation, documentation, and interviews. The overall results of this study state that the loose part-based labyrinth media can be used as a learning media referring to the results of the validation test and small and large group trials.